Physicochemical Quality Changes in Tomatoes during Delayed Cooling and Storage in a Controlled Chamber - Md. Shaha Nur Kabir; Mohammod Ali; Wang-Hee Lee; Seong-In Cho; Sun-Ok Chung (Agriculture, 2020)
The exposure of tomato fruits to unfavorable environments during the postharvest could result in severe losses along the supply chain. In this research, four tomato cultivars were stored in a controlled chamber under three levels of postharvest conditions to investigate the effects of delayed cooling on selected physicochemical quality parameters of the tomatoes. The tomato cultivars were subjected to three postharvest treatments: Immediate storage (IS) at harvest day; delayed storage (DS), leaving tomatoes without cover for one day; and under cover (DSC), separately in a greenhouse, and then stored in a controlled chamber at a temperature of 10 ± 1 °C and relative humidity of 90% ± 3%. Fresh weight, firmness, total soluble solids (TSS), and hue angle (h°) were examined over 15 days, every 5 days. Among the tomato cultivars, Cherry (7160), treated under DS showed the highest weight loss (13.01%) and firmness loss (42.14%) after 15 days of storage. Dabol (large) tomatoes treated with DS showed higher changes in TSS (°Bx) values (4.79 to 5.76). Low changes in hue angle values were found in IS-treated Cherry (7160) tomatoes at the end of the storage period. Overall quality changes were slower for all tomato cultivars treated with IS than with other treatments throughout the storage period. This study indicated the importance of reducing cooling delays to maintain the quality during the postharvest and prolong storage of harvested tomatoes.